Diminished Ost3-dependent N-glycosylation of the BiP nucleotide exchange factor Sil1 is an adaptive response to reductive ER stress - Stevens, K.; Black, A.; Wells, K.; Yeo, K.; Steuart, R.; Stirling, C.; Schulz, B.; Mousley, Carl (National Academy of Sciences, 2017)
© 2017, National Academy of Sciences. All rights reserved. BiP (Kar2 in yeast) is an essential Hsp70 chaperone and master regulator of endoplasmic reticulum (ER) function. BiP’s activity is regulated by its intrinsic ATPase activity that can be stimulated by two different nucleotide exchange factors, Sil1 and Lhs1. Both Sil1 and Lhs1 are glycoproteins, but how N-glycosylation regulates their function is not known. Here, we show that N-glycosylation of Sil1, but not of Lhs1, is diminished upon reductive stress. N-glycosylation of Sil1 is predominantly Ost3-dependent and requires a functional Ost3 CxxC thioredoxin motif. N-glycosylation of Lhs1 is largely Ost3-independent and independent of the CxxC motif. Unglycosylated Sil1 is not only functional but is more effective at rescuing loss of Lhs1 activity than N-glycosylated Sil1. Furthermore, substitution of the redox active cysteine pair C52 and C57 in the N terminus of Sil1 results in the Doa10-dependent ERAD of this mutant protein. We propose that reductive stress in the ER inhibits the Ost3-dependent N-glycosylation of Sil1, which regulates specific BiP functions appropriate to the needs of the ER under reductive stress.